2009
DOI: 10.1007/bf03175127
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential of a marine seaweedAsparagopsis taxiformis againstLeptospira javanica isolates of rodent reservoirs

Abstract: In this present investigation pharmacologically active compounds were isolated from red algae (Asparagopsis taxiformis) and their efficacy was evaluated against the Leptospira javanica isolates of rodent carriers. The GC-MS analysis of the purified compound revealed the presence of 4,5-dimethyl-1H-pyrrole-2-carboxylic acid ethyl ester (56.012%), fattyacids, 14-methyl-pentadecanoic acid methyl ester (26.6%), octadecanoic acid methyl ester (8.46%), octadec-9-enoic acid 2,3-dihydroxy-propyl ester (4.11%), 9-octad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Indeed, fatty acids inhibit enzyme activities, disrupt the electron transport chain and oxidative phosphorylation, and interfere with cellular energy production in microbes. They also damage nutrient uptake, generate peroxidation and auto-oxidation degradation products or direct lyse bacterial cells (Lee et al, 2009;Vedhagiri et al, 2009;Plouguerné et al, 2013). Many fatty acids demonstrate good antioxidant activities (Henry et al, 2002).…”
Section: Topical Issue 1 Introductionmentioning
confidence: 99%
“…Indeed, fatty acids inhibit enzyme activities, disrupt the electron transport chain and oxidative phosphorylation, and interfere with cellular energy production in microbes. They also damage nutrient uptake, generate peroxidation and auto-oxidation degradation products or direct lyse bacterial cells (Lee et al, 2009;Vedhagiri et al, 2009;Plouguerné et al, 2013). Many fatty acids demonstrate good antioxidant activities (Henry et al, 2002).…”
Section: Topical Issue 1 Introductionmentioning
confidence: 99%
“…This cocktail of metabolites is sequestered in specialized structures known as gland cells and may represent 2%-6% of the algal dry weight (Wolk 1968, Fenical 1975, Paul et al 2006). The high diversity and quantity of halogenated metabolites probably relate to the remarkable antimicrobial activity shown by Asparagopsis extracts when tested against human and animal pathogens (Bansemir et al 2006, Salvador et al 2007, Vedhagiri et al 2009). Since their discovery, research on the biological properties of halogenated compounds has shown antibacterial, antiviral, antifungal, anti-inflammatory, antifouling, cytotoxic, ichthyotoxic, and insecticidal activity (Blunt et al 2009).…”
mentioning
confidence: 99%
“…), spirochaete bacteria of clinical importance (Vedhagiri et al . ), fish and shellfish pathogenic bacteria (Genovese et al . ), shrimp Vibrio pathogens and plant pathogenic fungi (Manilal et al .…”
Section: Discussionmentioning
confidence: 99%